MEMBANGUN KELAS MASA KINI: URGENSI KETERAMPILAN KOMUNIKASI PENDIDIK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Ismira Ismira; Seri Sufani; Putri Yulia Mandasari; Wendri Gusdi; Mulya Syafrina; Febrio Rozalmi Putra; Yusparni Yetti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educators' communication skills are a crucial foundation in creating an effective, interactive, and student-centered learning process. In the 21st-century education era, teachers are required not only to master the learning material but also to communicate clearly, empathetically, and adaptively to students' needs. This literature review article discusses the essence of teachers' communication skills, their urgency in the learning process, and how effective communication can enhance motivation, concept understanding, and positive relationships between teachers and students. The review results show that good educator communication is directly related to increased student engagement, learning outcomes, and the creation of a conducive classroom environment. The practical implications of this study provide recommendations for educators to continuously develop verbal and nonverbal communication skills through professional training and reflection on teaching practices.